Antibacterial Activity of Electrospun Polyacrylonitrile Copper Nanoparticle Nanofibers on Antibiotic Resistant Pathogens and Methicillin Resistant Staphylococcus aureus (MRSA) - William B. Wang; Jude C. Clapper (Nanomaterials, 2022)
Bacteria induced diseases such as community-acquired pneumonia (CAP) are easily transmitted through respiratory droplets expelled from a person’s nose or mouth. It has become increasingly important for researchers to discover materials that can be implemented in in vitro surface contact settings which disrupt bacterial growth and transmission. Copper (Cu) is known to have antibacterial properties and have been used in medical applications. This study investigates the antibacterial properties of polyacrylonitrile (PAN) based nanofibers coated with different concentrations of copper nanoparticles (CuNPs). Different concentrations of copper sulfate (CuSO4) and polyacrylonitrile (PAN) were mixed with dimethylformamide (DMF) solution, an electrospinning solvent that also acts as a reducing agent for CuSO4, which forms CuNPs and Cu ions. The resulting colloidal solutions were electrospun into nanofibers, which were then characterized using various analysis techniques. Methicillin-Resistant isolates of Staphylococcus aureus, an infective strain that induces pneumonia, were incubated with cutouts of various nanocomposites using disk diffusion methods on Luria-Bertani (LB) agar to test for the polymers’ antibacterial properties. Herein, we disclose that PAN-CuNP nanofibers have successfully demonstrated antibacterial activity against bacteria that were otherwise resistant to highly effective antibiotics. Our findings reveal that PAN-CuNP nanofibers have the potential to be used on contact surfaces that are at risk of contracting bacterial infections, such as masks, in vivo implants, or surgical intubation.